Preparation and application of soy protein isolate-filled sucrose composite particles in sugar-reduced chocolate via protein-mediated morphological modulation - Yanke Wang; Sizhe Dong; Jinmei Wang; Jian Guo; Xiaoquan Yang (Food Research International, 2026)

Bifunctional N/O-doped porous carbons:Electron localization enables efficient adsorption and electron delocalization boosts PMS activation - Mingwei Yang; Maoguo Tan; Denghong Zhao; Hang Liu; Hongji Chen; Tao Liao; Jia Zeng; Yanke Jiang; Lixia Guo; Bin Sun; Heyan Jiang (Environmental Research, 2026)

Engineering carbon dots with amplified peroxidase-mimetic activity for dual-modal colorimetric-photothermal sensing of organophosphorus and carbamate pesticides - Na Gao; Yajuan Zhao; Yuhan Huang; Yanke Zhou; Linlin Yang; Liguo Ji; Hao Zhu; Wenjie Ren; Guangjie He (Analytica Chimica Acta, 2026)

Hydrothermal dynamics evolution of dry-hot valleys under multiple impacts - Yuankun Wang; Weiguo Ma; Yang You; Lei Zhao; Yanke Zhang; Dong Wang (Journal of Environmental Management, 2026)

Defect and multi-interface synergistic engineering of a sulfide heterostructure with spatially separated redox sites enabling efficient and stable photocatalytic H2 evolution - Yachong Wang; Chaoyue Zheng; Youlin Wu; Qingyang Pang; Yanke Yang; Jihuai Wu; Meihua Xin; Cheng Peng; Jiamin Lu; Yiming Xie (Chemical Engineering Journal, 2026)

Quantifying the drivers of river thermal regimes in the Hanjiang River Basin under climate change and reservoir construction - Lei Zhao; Yuankun Wang; Yang You; Sen Wang; Yixu Wang; Changqing Meng; Yanke Zhang; Dong Wang (Journal of Hydrology, 2026)

Long-term spatiotemporal heterogeneity and drivers of lake thermal dynamics in the Yangtze river basin - Yuankun Wang; Weiguo Ma; Jiaxin Tao; Yang You; Lei Zhao; Yanke Zhang; Dong Wang (Environmental Research, 2026)

Chickpea sourdough as a functional ingredient in gluten-free bread: Impact on quality attributes - Ruixue Jiang; Zimu Lin; Honghao Shi; Yan Wang; Yanke Wang; Qiang Yang (Food Hydrocolloids, 2026)

A highly efficient nanocopper hydroxide activates plant immune resistance and confers tolerance to salt and drought stress in rice - Chongchong Lu; Zimeng Li; Taizhong Huang; Muhammad Zunair Latif; Haifeng Liu; Mingxia Hao; Yanke Jiang; Yingzhe Yue; Jian Zhang; Miaomiao Deng; Qian Du; Sifan Yang; et al. (Chemical Engineering Journal, 2026)

Unveiling river thermal regimes in the Yangtze river basin, China, with a hybrid deep learning model - Yang You; Yuankun Wang; Jiaxin Tao; Lei Zhao; Sen Wang; Yanke Zhang; Changqing Meng; Dong Wang (Journal of Environmental Management, 2026)

Vacancy defect regulation of the spatial local electronic states and energy band structure of CoNi₂S₄/VsCdS Schottky junction for improved photocatalytic hydrogen evolution - Qingyang Pang; Youlin Wu; Yanke Yang; Jihuai Wu; Jiamin Lu; Yiming Xie (Chemical Engineering Journal, 2025)

Corrigendum to “Main lipid sources affecting key aroma volatile compounds in Chinese native chicken” [Food Chemistry 474 (2025) 142990] - Yanji Chen; Yongli Wang; Yanke Wang; Na Luo; Richun Cai; Yang Yu; Xu Zhang; Jinmei Zhu; Guiping Zhao; Jie Wen; Huanxian Cui (Food Chemistry, 2025)

Main lipid sources affecting key aroma volatile compounds in Chinese native chicken - Yanji Chen; Yongli Wang; Yanke Wang; Na Luo; Richun Cai; Yang Yu; Xu Zhang; Jinmei Zhu; Guiping Zhao; Jie Wen; Huanxian Cui (Food Chemistry, 2025)

Impact of the potassium transporter TaHAK18 on wheat growth and potassium uptake under stressful K+ conditions - Tengfei Liu; Yanan Zhang; Yumin Xie; Ruipeng Yang; Mengying Yuan; Yanke Li; Haixia Xu; Xinli Zhu; Tengzhao Song; Xiyong Cheng (Journal of Plant Physiology, 2025)

Synergistic construction of efficient heterojunction structures through vacancy engineering and nanoscale effects to enhance photodegradation efficiency - Qingyang Pang; Chaoyue Zheng; Youlin Wu; Xuan Wang; Yachong Wang; Yanke Yang; Teng Li; Canzhong Lu; Yiming Xie; Fuda Yu (Journal of Water Process Engineering, 2025)

Role of ocean-atmosphere interaction in intraseasonal variability of summer rainfall over the Indo–Northwest Pacific - Yang Wang; Zhen-Qiang Zhou; Renhe Zhang; Yanke Tan (Climate Dynamics, 2024)

Comparison of two filter approaches for characterizing boreal summer intraseasonal oscillation - Yang Wang; Zhen-Qiang Zhou; Renhe Zhang; Yanke Tan (Atmospheric Research, 2024)

Identification of characteristic aroma compounds in chicken meat and their metabolic mechanisms using gas chromatography–olfactometry, odor activity values, and metabolomics - Yanke Wang; Li Liu; Xiaojing Liu; Yidong Wang; Weifang Yang; Wenjuan Zhao; Guiping Zhao; Huanxian Cui; Jie Wen (Food Research International, 2024)

Correction to: Further inquiry into the interaction between the winter North Pacific storm track and the East Asian trough - Minghao Yang; Chongyin Li; Yanke Tan; Xin Li; Xiong Chen; Peilong Yu (Climate Dynamics, 2020)

Further inquiry into the interaction between the winter North Pacific storm track and the East Asian trough - Minghao Yang; Chongyin Li; Yanke Tan; Xin Li; Xiong Chen; Peilong Yu (Climate Dynamics, 2020)
Based on the daily ERA-Interim reanalysis, interactions between the winter North Pacific storm track (WNPST) and the East Asian trough (EAT) on the interannual scale are further explored from the perspective of energy conversion and the simplified quasi-geostrophic potential vorticity equation. There is a prominent out-of-phase relationship between the EAT and WNPST on the interannual scale. It is baroclinic energy conversion rather than barotropic energy conversion that is the main physical process that the EAT affects the WNPST. When the EAT is intensified, the energy conversion from mean available potential energy to eddy available potential energy decreases; further, the energy conversion from eddy available potential energy to eddy kinetic energy is attenuated, which leads directly to remarkable weakening in the strength of the WNPST in its peak area and the region west of the date line. In addition, when the WNPST is enhanced, the WNPST dynamic forcing contributes to lowering the geopotential height near the EAT and thus profits to recover the strength of the EAT, while the thermal forcing of WNPST is opposite. However, their joint effect is still to strengthen the EAT, indicating that the impact of WNPST dynamic forcing on the EAT is stronger than that of thermal forcing. The interaction between the WNPST and EAT may be a way for the WNPST to maintain itself.

Involvement of MEM1 in DNA demethylation in Arabidopsis - Yanke Lu; Jie Dai; Liu Yang; Yumei La; Shaoxia Zhou; Sheng Qiang; Qianqian Wang; Feng Tan; Yufeng Wu; Weiwen Kong; Honggui La (Plant Molecular Biology, 2020)

Influence of cumulus convection schemes on winter North Pacific storm tracks in the regional climate model RegCM4.5 - Minghao Yang; Yanke Tan; Xin Li; Xiong Chen; Chao Zhang; Peilong Yu (International Journal of Climatology, 2020)
Based on the regional climate model RegCM4.5 driven by National Centers for Environmental Prediction (NCEP) reanalysis, the influence of cumulus convection schemes (CCSs) on the winter North Pacific storm track (WNPST) is investigated. It is found that the climatology, interannual variation, spatial modes and characteristic indices of the WNPST are extremely sensitive to the choice of CCS. Among the selected CCSs, WNPST climatology and interannual variation in the Kuo scheme are better than in other CCSs, with a smaller root mean square error. The WNPST spatial modes and strength indices in the Kuo and Grell schemes are more consistent with NCEP reanalysis. The Kuo scheme has a stronger ability to simulate the WNPST latitude index and the interannual variation of winter characteristic indices. In addition, we attempt to reveal the possible reasons for the different performances of CCSs from the viewpoint of baroclinic energy conversion (BCEC). It is found that the energy conversion from the mean available potential energy to the eddy available potential energy (BCEC1) has no significant difference among the Kuo, Grell and Emanuel schemes, while energy conversion from the eddy available potential energy to eddy kinetic energy (BCEC2) in the Kuo scheme is obviously better than other CCSs, which means that the differences in BCEC2 among these CCSs may be one of the key reasons affecting the simulation results of the WNPST.

Remote impact of North Atlantic sea surface temperature on rainfall in southwestern China during boreal spring - Gang Li; Jiepeng Chen; Xin Wang; Xia Luo; Daoyong Yang; Wen Zhou; Yanke Tan; Hongming Yan (Climate Dynamics, 2018)

Diagnosis of moist vorticity and moist divergence for a heavy precipitation event in Southwestern China - Gang Li; Daoyong Yang; Xiaohua Jiang; Jing Pan; Yanke Tan (Advances in Atmospheric Sciences, 2017)

Association of Microtubule Dynamics with Chronic Epilepsy - Xin Xu; Yida Hu; Yan Xiong; Zhonggui Li; Wei Wang; Chao Du; Yong Yang; Yanke Zhang; Fei Xiao; Xuefeng Wang (Molecular Neurobiology, 2016)

Applications of Human Pharmacokinetic Prediction in First-in-Human Dose Estimation - Peng Zou; Yanke Yu; Nan Zheng; Yongsheng Yang; Hayley J. Paholak; Lawrence X. Yu; Duxin Sun (The AAPS Journal, 2012)

A new method for calculating the wind speed distribution of a moving tropical cyclone - Banghui Hu; Xiuqun Yang; Yanke Ttan; Yongqing Wang; Yong Fan (Advances in Atmospheric Sciences, 2010)